А Study of “City-Language” - Авина, Н. Ю. (Kalbotyra, 1992)
The paper deals with an important problem of contemporary Slavonic studies - investigation of “City-Language”. In the paper some observations on one of the varieties of spoken language - Russian popular speech in Vilnius - submitted for consideration. The most typical lexico - semantical features of spoken Russian are under investigation. The noted regional popular speech is a very complicated phenomennon, which under a specific influence of the local dialects.